Establishing reference intervals for common hematology test parameters from apparently healthy geriatrics in Asella town, Southeast Ethiopia, 2020: a community-based cross-sectional study - Hashim Harka, Mohammed; Siraj, Zuber; Dibaba, Berhanu; Zerihun Mamo, Tewodros; Ajema, Bayyisa; Tsegaye, Aster; Wordofa, Moges (Frontiers in Medicine, 2024)
Background Reference intervals are an important method tool for identifying abnormal laboratory test results. Complete blood count reference values are useful to interpret complete blood count (CBC) results and make clinical decisions, but these values have not been established for geriatrics in Asella town. Therefore, this study aimed to establish reference intervals (RIs) for complete blood count (CBC) parameters from geriatric participants/subjects in Asella town, Southeast Ethiopia. Methods A community-based cross-sectional study was conducted from December 2019 to May 2020. An interviewer-administered questionnaire was used to collect data on sociodemography and other characteristics from 342 eligible geriatric participants. Weight, height, and vital signs were measured, and 8 mL of blood sample was collected. Screening tests such as HIV, HBsAg, HCV, syphilis, stool examination, and urinalysis were performed. The hematological parameter was measured using a Sysmex kx-21 hematology analyzer. The data were analyzed using SPSS version 21 software. The non-parametric independent Kruskal–Wallis test and Wilcoxon rank-sum test (Mann–Whitney U test) were used to compare the parameters between age groups and genders. The 97.5 and 2.5th percentile were the upper and lower reference limit for the population. Results According to the study’s findings, the reference intervals of red blood cell, white blood cell, platelet count, hemoglobin (HGB), and hematocrit (HCT) in male geriatrics were 3.8–5.85 × 1012/L, 3.1–9.66 × 109/L, 115.8–353 × 109/L, 12.4–17.76 g/dL, and 35.06–50.2%, respectively. The respective values for women were 3.94–5.48 × 1012/L, 3.13–8.4 × 109/L, 137.5–406 × 109/L, 12.5–16.4 g/dL, and 36.09–48.2%. Most of the hematological parameters showed significant differences between the two genders (p value <0.05). Conclusion Accurate gender and age-specific reference intervals are crucial in managing patient health. The current study offers essential CBC hematological parameters that can assist clinicians in interpreting laboratory results and can improve healthcare quality in the geriatric population. Therefore, it is more relevant to use the current RIs in the geriatric set-up.